Perancangan Aplikasi e-Lades sebagai Sistem Pelayanan Administrasi Masyarakat Berbasis Website di Desa XYZ menggunakan Metode Rapid Application Development - Demonius Sarumaha; Junaidi (Universitas Budi Darma, 2025)
Public administration services in Desa Amplas are still conducted manually, resulting in delays, lack of transparency. This study aims to design and develop the e-Lades (Electronic Village Service) web-based application to improve efficiency, effectiveness, and accountability of services. The development method used is Rapid Application Development (RAD), allowing fast iterations based on user feedback. The research stages include requirements analysis, system design, development, testing, implementation, and evaluation. The main features include online administrative document registration, population data management, application status tracking, and WhatsApp-based automatic notifications. Trial results show an increase in service processing speed by up to 60% compared to the manual system, and an 85% increase in community satisfaction. This application is expected to serve as a model for digitizing village administrative services that can be replicated in other areas